Efficiency of the research and development activities of technical universities in Poland - Łącka, Irena; Brzezicki, Łukasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
In the 21st century knowledge-based economy, long-term economic growth and development depend on the ability to use the knowledge and technology so as to create product, process, organisational, marketing and even social innovations. The knowledge and technology, human resources and social capital (facilitating the transfer of technology from the world of science to the economy), comprise the most important production factors today. Research and development (R&D) activities are among the diverse determinants affecting the economy’s ability to innovate. They are carried out by public technical universities. One of the tasks that these entities face is to conduct basic, industrial (applied) research and development works. Their results can then be transferred to industrial and service enterprises as novel solutions. Research and development activities of universities are financed mainly from public sources, which suggests the need to assess the efficiency of this task. This can be done with the use of various methods, e.g. the non-parametric DEA method. The purpose of the paper is to measure the efficiency of research and development activities of public technical universities in Poland with the aid of the DEA method. The fourteen universities which in the years 2015–2017 reported to the Ministry of Science and Higher Education (MNiSW) were included in the study. The efficiency of the universities in filing new patent solutions and being granted patents was analysed. The results acquired indicate very low and low efficiency of most Polish technical universities. This is due both to a small number of patent applications and a small number of patents granted. In the examined period, the group of most efficient technical universities in both aspects comprised 4 to 5 universities.

W gospodarce XXI w. opartej na wiedzy, długookresowy wzrost i rozwój gospodarczy zależą od umiejętności wykorzystywania wiedzy i technologii do tworzenia innowacji produktowych, procesowych, organizacyjnych, marketingowych, a nawet społecznych. Wiedza i technologia, kapitał ludzki oraz społeczny (umożliwiający transfer technologii ze świata nauki do gospodarki), stanowią dziś najważniejsze czynniki wytwórcze. Wśród różnych determinant wpływających na zdolność gospodarki do innowacji znajduje się działalność badawczo-rozwojowa (B+R) realizowana przez publiczne szkoły wyższe, m.in. uczelnie techniczne. Jednym z zadań tych podmiotów jest prowadzenie badań podstawowych, przemysłowych (stosowanych) i prac rozwojowych. Ich rezultaty powinny trafiać do przedsiębiorstw przemysłowych i usługowych jako możliwe do wykorzystania nowe rozwiązania. Działalność badawczo-rozwojowa szkół wyższych jest finansowana głównie ze źródeł publicznych, co skłania do próby oceny efektywności wykonywania tego zadania. Można to zrealizować za pomocą różnych metod, np. nieparametrycznej metody DEA. Celem artykułu jest pomiar za pomocą metody DEA efektywności działalności badawczo-rozwojowej publicznych uczelni technicznych w Polsce. Do badania przyjęto 14 uczelni, które podlegały w latach 2015–2017 Ministerstwu Nauki i Szkolnictwa Wyższego (MNiSW). Przeanalizowano efektywność szkół wyższych odnośnie do zgłaszania nowych rozwiązań patentowych oraz uzyskanych patentów. Uzyskane wyniki wskazują na bardzo niską i niską efektywność większości polskich szkół technicznych. Wynika to zarówno z małej liczby zgłoszeń patentowych, jak i małej liczby uzyskiwanych patentów. W badanym okresie grupa najbardziej efektywnych uczelni technicznych w obu aspektach liczyła jedynie 4–5 jednostek.
Keywords: R&D; efficiency; universities; DEA; B+R; efektywność; szkoły wyższe